A role for hepatic leptin signaling in lipid metabolism via altered very low density lipoprotein composition and liver lipase activity in mice12. Issue 2 (6th December 2012) - Huynh, Frank K.; Neumann, Ursula H.; Wang, Ying; Rodrigues, Brian; Kieffer, Timothy J.; Covey, Scott D.
Abstract Obesity is highly associated with dyslipidemia and cardiovascular disease. However, the mechanism behind this association is not completely understood. The hormone leptin may be a molecular link between obesity and dysregulation of lipid metabolism. Leptin can affect lipid metabolism independent of its well‐known effects on food intake and energy expenditure, but exactly how this occurs is ill‐defined. We hypothesized that since leptin receptors are found on the liver and the liver plays an integral role in regulating lipid metabolism, leptin may affect lipid metabolism by acting directly on the liver. To test this hypothesis, we generated mice with a hepatocyte‐specific loss of leptin signaling. We previously showed that these mice have increased insulin sensitivity and elevated levels of liver triglycerides compared with controls. Here, we show that mice lacking hepatic leptin signaling have decreased levels of plasma apolipoprotein B yet increased levels of very low density lipoprotein (VLDL) triglycerides, suggesting alterations in triglyceride incorporation into VLDL or abnormal lipoprotein remodeling in the plasma. Indeed, lipoprotein profiles revealed larger apolipoprotein B‐containing lipoprotein particles in mice with ablated liver leptin signaling. Loss of leptin signaling in the liver was also associated with a substantial increase in lipoprotein lipase activity in the liver, which may have contributed to increased lipid droplets in the liver. Conclusion: Lack of hepatic leptin signaling results in increased lipid accumulation in the liver and larger, more triglyceride‐rich VLDL particles. Collectively, these data reveal an interesting role for hepatic leptin signaling in modulating triglyceride metabolism. (HEPATOLOGY 2013)